Association of lipoprotein lipase (LPL) single nucleotide polymorphisms with type 2 diabetes mellitus - Cho, Yoon Shin (Korean Society of Medical Biochemistry and Molecular Biology, 2008)
The etiology and pathogenesis of type 2 diabetes mellitus (T2DM) are not completely understood although it is often associated with other conditions such as obesity, hypertension, and dyslipidemia. Lipoprotein lipase (LPL) is a key enzyme in human lipid metabolism that facilitates the removal of triglyceride-rich lipoproteins from the bloodstream. LPL hydrolyzes the core of triglyceride-rich lipoproteins (chylomicrons and very low density lipoprotein) into free fatty acids and monoacylglycerol. To gain insight into the possible role of LPL in T2DM, nine single nucleotide polymorphisms (SNPs) of LPL were analyzed for the association with T2DM using 944 unrelated Koreans, including 474 T2DM subjects and 470 normal healthy controls. Of the nine LPL SNPs we analyzed, a significant association with multiple tests by the false discovery rate (FDR) was observed between T2DM and SNP rs343 (+13836C>A in intron 3). SNP rs343 was also marginally associated with some of T2DM-related phenotypes including total cholesterol, high density lipoprotein cholesterol (HDLc), and log transformed glycosylated hemoglobin in 470 normal controls, although no significant association was detected by multiple tests. In total, our results suggest that the control of lipid level by LPL in the bloodstream might be an important factor in T2DM pathogenesis in the Korean population.